Explaining the period fluctuation of the quasi-biennial oscillation - Y.-H. Kim (Atmospheric Chemistry and Physics)
The tropical stratosphere is characterized by a periodic oscillation of wind direction between westerly and easterly, known as the quasi-biennial oscillation (QBO), which modulates middle atmospheric circulations and surface climate on interannual timescales. The oscillation period fluctuates irregularly, ranging from 20 to 35 months. The causes of this fluctuation have long been hypothesized but lack observational evidence. This study shows that the period fluctuation is primarily driven by variability in small-scale wave (gravity wave) activity with an additional contribution from variability in tropical upwelling. Using an atmospheric reanalysis dataset, we capture temporal variations in small-scale wave activity that are coherent with the varying speed of the oscillation. This wave activity variation stems from the seasonality of tropical convection and tropopause layer wind, revealing their fundamental role in modulating the quasi-biennial period. Our findings suggest that better representing these multiscale interactions in models can enhance the accuracy of seasonal forecasts and the reliability of future climate projections.